2018
DOI: 10.1371/journal.pone.0195826
|View full text |Cite
|
Sign up to set email alerts
|

Effect of one-lung ventilation on end-tidal carbon dioxide during cardiopulmonary resuscitation in a pig model of cardiac arrest

Abstract: Unrecognized endobronchial intubation frequently occurs after emergency intubation. However, no study has evaluated the effect of one-lung ventilation on end-tidal carbon dioxide (ETCO2) during cardiopulmonary resuscitation (CPR). We compared the hemodynamic parameters, blood gases, and ETCO2 during one-lung ventilation with those during conventional two-lung ventilation in a pig model of CPR, to determine the effect of the former on ETCO2. A randomized crossover study was conducted in 12 pigs intubated with d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…In our experience, 20% of an animal's anteroposterior chest diameter was the maximum chest compression depth for avoiding critical injuries related to CPR. Hence, this depth was used as optimal chest compression depth in our previous studies using a swine model of CPR . During CPR, asynchronous positive‐pressure ventilations with high‐flow oxygen (15 L/min) were provided at a rate of 10 breaths/min using a volume‐marked manual resuscitator bag .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In our experience, 20% of an animal's anteroposterior chest diameter was the maximum chest compression depth for avoiding critical injuries related to CPR. Hence, this depth was used as optimal chest compression depth in our previous studies using a swine model of CPR . During CPR, asynchronous positive‐pressure ventilations with high‐flow oxygen (15 L/min) were provided at a rate of 10 breaths/min using a volume‐marked manual resuscitator bag .…”
Section: Methodsmentioning
confidence: 99%
“…Hence, this depth was used as optimal chest compression depth in our previous studies using a swine model of CPR. 26,27 During CPR, asynchronous positive-pressure ventilations with high-flow oxygen (15 L/min) were provided at a rate of 10 breaths/min using a volume-marked manual resuscitator bag. 28 Coinciding with the start of chest compressions, either a saline placebo (control group) or pralidoxime solution (pralidoxime group) was administered into the RA.…”
Section: Study To Investigate the Effects Of Pralidoxime Administermentioning
confidence: 99%
“…Several studies have been conducted on ETCO 2 during CPR in animal models. In one study, ETCO 2 was significantly lower during right lung ventilation than during ventilation of both the lungs and ventilation of the left lung [12]. Another study reported that ETCO 2 during extracorporeal cardiopulmonary resuscitation may be predictive of the extent of brain or kidney damage [13,14].…”
Section: Discussionmentioning
confidence: 99%
“…However, maintenance of adequate vision during intubation can be challenging for clinicians, particularly in high-tension environments and with the physical barriers of PPE. In addition, instant capnography check does not guarantee the avoidance of endobronchial intubation ( 14 – 16 ). For instance, hypoxemia may occur later, ( 15 ) and capnography measurements may not change in endobronchial intubation ( 14 , 16 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, instant capnography check does not guarantee the avoidance of endobronchial intubation ( 14 – 16 ). For instance, hypoxemia may occur later, ( 15 ) and capnography measurements may not change in endobronchial intubation ( 14 , 16 ). Nevertheless, our results indicated that most of the auscultation test failures (76.9%) occurred because the participant anesthesiologist was unable to confirm bilateral symmetric lung sound, regardless of the auscultation method.…”
Section: Discussionmentioning
confidence: 99%